Comparison of Clinical Outcomes Between Laparoscopic and Open Surgery in Colorectal Cancer Patients - Swapnil Saraiya; Dhara Darji (Wolters Kluwer Medknow Publications, 2024)
Aim: Our research compares the clinical results of open surgery versus laparoscopic surgery for colorectal malignancies. Materials and Methods: Our analysis focused on a database that included data on patients with colorectal cancer who had laparoscopic or open surgery for stages I to III at a prestigious healthcare institute in India. Two groups of 50 patients underwent laparoscopic and 50 underwent conventional open colorectal surgery (OCRS and LCRS, respectively) throughout the same time. Patient demographics, operation data, initial postoperative outcomes, follow-up appointments, pathology results, and cancer stages were examined. Results: The LCRS group had a much longer operation time compared to the OCRS. Subjects in the LCRS group experienced a notably accelerated recovery after surgery. The hospital stay for the OCRS group was considerably longer compared to that in the LCRS group. Conclusion: Laparoscopic colorectal surgery is a reliable and convenient alternative to the traditional open approach, providing comparable oncological efficacy.